Prevalence, risk factors and impact of occult HCV infection on liver morbidity among haemodialysis patients: hospital-based cross-sectional study. (2nd August 2020) - Alduraywish, Abdulrahman; Ragheb, Mostafa; Taher, Ibrahim; Louis, Nageh; Aldossari, Khaled; Kishk, Rania
Abstract: Objectives: Haemodialysis (HD) patients are at risk for blood-borne infections as occult HCV infection, which justifies comprehensive studies. We aimed to determine the prevalence and risk factors of occult HCV infection (OCI) among HD patients. Material and methods: One hundred eligible HD patients, with no evidence of overt HCV or HBV and HBV vaccinated were recruited, and tested for HCV, HBV markers and HCV RNA. Two HCV-positive patients were excluded and peripheral mononuclear cells of 98 patients were verified for viraemia. Results: OCI was detected in eight (8.16%); with a median viral load of 7010copies/ml. Their mean age was 30.63 (±18.87 years) compared to others (41.73 ± 15.93) ( p = .069). History of surgery, dental procedure, and blood transfusion was comparably high in both groups ( p > .05). All OCI patients underwent dialysis twice weekly compared to 48.9% of non-OCI patients ( p = .006). OCI patients had a significantly higher mean duration of dialysis (12.63 ± 6.74 years), and a significantly higher frequency (50%) of HCV Ab compared to 6.48 ± 4.76, and 10%, respectively, in non-OCI patients. None of OCI patients was reactive to HBcAb compared to 34 (37.8%) patients without ( p = .048). Evidence of liver morbidity was detected in 5 (62.5%) OCI patients compared to 43 (47.7%) of non-OCI patients ( p > .05). Conclusion: Among our HD patients, OCI is considered a comorbid finding associated with mild liver morbidity that warrants strict infection control and periodic testing for blood borne infections.